Методы повышения экономичности магистральных насосных агрегатов, имеющих привод от электродвигателя - Gavrilov D. I., Ovsiannikov E. I. (Student science of the XXI century, 2016)
The article describes the basic methods of optimization and enhance the efficiency of the main pumps with electric drive.
Keywords: экономия электроэнергии; магистральные насосы; электродвигатели; электроприводы; main pumps; electric motors; electric drives; energy savings